The Styles of the Artists Creating in the Landscape Genre Analysis - Qizi, Rahimova Madina Yashnarjon (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article talks about the attention given to the field of art, the analysis of the styles of the artists who created in the landscape genre, and the feeling of the image with the whole body, leaving an indelible mark on the field of visual art of our country.